2006
DOI: 10.1590/s0100-46702006000100006
|View full text |Cite
|
Sign up to set email alerts
|

Thermal degradation behaviour of some polydithiooxamide metal complexes

Abstract: IntroductionThe well-established thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC) techniques have been reliably widely used over many decades in studying the thermal behaviour and properties of various types of materials and evaluating the thermal parameters for their degradation processes. These methods have allowed determination of the chemical steps of the investigated degradation and the evaluation, by some methods [1,2], of the kinetic parameters for each step. The evaluation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 18 publications
2
12
0
Order By: Relevance
“…Their activation energies found to be 98 and 242 kJ mol -1 , respectively. It is found that the release of the coordinated water molecules and chloride atoms fairly accord with literature [42,43].…”
Section: Thermal Analysissupporting
confidence: 86%
“…Their activation energies found to be 98 and 242 kJ mol -1 , respectively. It is found that the release of the coordinated water molecules and chloride atoms fairly accord with literature [42,43].…”
Section: Thermal Analysissupporting
confidence: 86%
“…Theoretically the calculated these values are different for polymer‐metal complexes as follows: 6.57%, 13.56%, 13.56%, 7.16%, 3.73%, and 14.46% for P‐2,3‐TP‐Cd, P‐2,3‐TP‐Co, P‐2,3‐TP‐Ni, P‐2,3‐TP‐Zn, P‐2,3‐TP‐Cu, and P‐2,3‐TP‐U. In this dehydration process, the ease of adsorbed water desolvation (20°C ≤ T ≤ 96°C) in these complexes suggests the weak interaction of water 37. Temperature ranges reported38–40 for the release of coordinated water molecules in some complexes (Fe, Ni, etc.).…”
Section: Resultsmentioning
confidence: 96%
“…After that coconut shell particles are treated with 5wt% of DAP solution and then mixed in resin and stirred mechanically by means of a high speed mechanical stirrer. Coconut shell and coconut shell particles are shown in the Figure 1 [5].…”
Section: Coconut Shell Particlesmentioning
confidence: 99%